Benign thyroid nodules respond to a single administration of 0.3mg recombinant human thyrotropin with highly variable volume increase - Bountouris, Panagiotis; Markantes, Georgios K.; Mamali, Irene; Markou, Kostas B.; Michalaki, Marina A. (Frontiers in Endocrinology, 2023)
Introduction: The nature of thyroid nodules is heterogenous. Most of them are benign and, in the absence of pressure symptoms of adjunct structures, no treatment is needed. Our objective was to investigate the acute effects of a low dose of recombinant human TSH (rhTSH) on the volume of benign thyroid nodules. Methods: we studied 27 nodules (14 isoechoic and 13 hypoechoic) in 15 (11 women and 4 men; mean age: 51.0±15.9 years) consecutive patients with one to three well-separated asymptomatic benign thyroid nodules. All subjects were euthyroid, with negative thyroid antibodies, and none received levothyroxine. The total thyroid volume and thyroid nodule volume were sonographically determined by two independent examiners (P.B. and M.M.) before, 48 hours and 6 months post intramuscular (IM) administration of 0.3mg rhTSH, and the mean values of the two examiners’ measurements were used; thyroid function tests were obtained at the same time points. Results: The mean volume of isoechoic nodules increased by 57.3%, of hypoechoic nodules by 46.6% and of the surrounding thyroid parenchyma by 70.4% 48 hours post-rhTSH; mean volumes had returned to baseline levels 6 months later. A large variance in the volume change responses was observed. The relative change in nodule volume (defined as the percent change in nodule volume divided by the percent change in the surrounding parenchyma) from baseline to 48 hours was significantly higher in isoechoic versus hypoechoic nodules (p<0.05). Conclusions: A single dose of 0.3 mg rhTSH transiently increased the volume of benign thyroid nodules. The increase was more pronounced in isoechoic nodules and had a great variability. Our findings could be useful in the management of benign thyroid nodules, by helping in understanding which nodules would be more responsive to TSH suppression therapy.